Numerical study of the fuel rod melting and molten material migration behavior using the MPS method - Yonglin Li; Sufen Li; Xingfu Cai; Yonggang Huo (AIP Advances)
The catastrophic consequences of nuclear reactor core meltdowns necessitate a comprehensive understanding of fuel rod behavior during severe accidents. This study employs the moving particle semi-implicit (MPS) method to simulate fuel rod melting and molten material migration, capturing complex phenomena such as phase changes, chemical reactions, and fluid dynamics. The developed MPS code integrates models for heat transfer, eutectic reactions, and surface tension, allowing for detailed three-dimensional simulations. Validation of the code is achieved through comparisons with analytical solutions and experimental data from the FROMA experiments. Simulations of Al–Zn substitute material rods show accurate temperature responses and phase transitions, highlighting the impact of radiation heat transfer and molten pool depth on melting behavior. Additional simulations of a single rod and a 2 × 2 rod bundle in a pressurized water reactor under extreme conditions reveal the significant role of atomic diffusion. Mass transfer between the cladding and fuel pellet expands the melting area and facilitates the formation of low-melting-point substances. The high-temperature behavior of the rod bundle demonstrates characteristic patterns, including the downward migration of molten zirconium and the dissolution of unmelted cladding. Analysis of molten UO2 migration within the rod bundle channel illustrates the influence of initial temperature and volume on migration dynamics and Zr cladding dissolution rates. This study offers valuable insights into understanding and mitigating the risks associated with core meltdowns, thereby enhancing nuclear reactor safety.